Clevidipine as a therapeutic and cost-effective alternative to sodium nitroprusside in patients with acute aortic syndromes. Issue 3 (October 2020) - Alviar, Carlos L; Gutierrez, Alejandra; Cho, Leslie; Krishnaswamy, Amar; Saleh, Amr; Lincoff, Michael A; Roselli, Eric; Militello, Michael; Menon, Venu
Background: Sodium nitroprusside is the preferred agent for the treatment of high blood pressure during acute aortic syndrome if blood pressure remains elevated after heart rate control with beta-blockers. The increasing cost of sodium nitroprusside in the USA led us to assess the efficacy and safety of intravenous clevidipine, a calcium channel blocker with quick onset of action, short half-life and significantly lower costs than sodium nitroprusside, in patients presenting with acute aortic syndrome. Methods: We performed a retrospective chart review of consecutive patients admitted to the Cleveland Clinic Cardiac Intensive Care Unit from 2013–2016 with a diagnosis of acute aortic syndrome. Patients who received intravenous sodium nitroprusside were compared with those receiving intravenous clevidipine. The primary outcome was a significant difference in blood pressure at one, three and six hours. Secondary outcomes included time to achieving blood pressure target and in hospital mortality with rates of hypotension and bradycardia as safety endpoints. Results: A total of 85 patients with suspected acute aortic pathology received clevidipine and 50 received sodium nitroprusside. Clinical and demographic characteristics were similar in both groups, except for a higher incidence of abdominal aortic aneurysm in the clevidipine group and for a trend towards higher use of labetalol in the clevidipine group. There were no significant differences in blood pressure or heart rate at one, three and six hours after starting either infusion. The rates of hypotension, bradycardia and in-hospital mortality did not differ. Time to achieve blood pressure control were also similar between groups. Conclusion: Intravenous clevidipine appears to be a safe and effective alternative to sodium nitroprusside for the management of high blood pressure during acute aortic dissection. In the USA, clevidipine could represent a cost effective therapy providing similar outcomes than sodium nitroprusside.